Intercomparison of NO3 radical detection instruments in the atmosphere simulation chamber SAPHIR - H.-P. Dorn; R. L. Apodaca; S. M. Ball; T. Brauers; S. S. Brown; J. N. Crowley; W. P. Dubé; H. Fuchs; R. Häseler; U. Heitmann; R. L. Jones; A. Kiendler-Scharr; et al. (Atmospheric Measurement Techniques, 2013)
The detection of atmospheric NO3 radicals is still challenging owing to its low mixing ratios (≈ 1 to 300 pptv) in the troposphere. While long-path differential optical absorption spectroscopy (DOAS) has been a well-established NO3 detection approach for over 25 yr, newly sensitive techniques have been developed in the past decade. This publication outlines the results of the first comprehensive intercomparison of seven instruments developed for the spectroscopic detection of tropospheric NO3. Four instruments were based on cavity ring-down spectroscopy (CRDS), two utilised open-path cavity-enhanced absorption spectroscopy (CEAS), and one applied "classical" long-path DOAS. The intercomparison campaign "NO3Comp" was held at the atmosphere simulation chamber SAPHIR in Jülich (Germany) in June 2007. Twelve experiments were performed in the well-mixed chamber for variable concentrations of NO3, N2O5, NO2, hydrocarbons, and water vapour, in the absence and in the presence of inorganic or organic aerosol. The overall precision of the cavity instruments varied between 0.5 and 5 pptv for integration times of 1 s to 5 min; that of the DOAS instrument was 9 pptv for an acquisition time of 1 min. The NO3 data of all instruments correlated excellently with the NOAA-CRDS instrument, which was selected as the common reference because of its superb sensitivity, high time resolution, and most comprehensive data coverage. The median of the coefficient of determination (r2) over all experiments of the campaign (60 correlations) is r2 = 0.981 (quartile 1 (Q1): 0.949; quartile 3 (Q3): 0.994; min/max: 0.540/0.999). The linear regression analysis of the campaign data set yielded very small intercepts (median: 1.1 pptv; Q1/Q3: −1.1/2.6 pptv; min/max: −14.1/28.0 pptv), and the slopes of the regression lines were close to unity (median: 1.01; Q1/Q3: 0.92/1.10; min/max: 0.72/1.36). The deviation of individual regression slopes from unity was always within the combined accuracies of each instrument pair. The very good correspondence between the NO3 measurements by all instruments for aerosol-free experiments indicates that the losses of NO3 in the inlet of the instruments were determined reliably by the participants for the corresponding conditions. In the presence of inorganic or organic aerosol, however, differences in the measured NO3 mixing ratios were detectable among the instruments. In individual experiments the discrepancies increased with time, pointing to additional NO3 radical losses by aerosol deposited onto the filters or on the inlet walls of the instruments. Instruments using DOAS analyses showed no significant effect of aerosol on the detection of NO3. No hint of a cross interference of NO2 was found. The effect of non-Lambert–Beer behaviour of water vapour absorption lines on the accuracy of the NO3 detection by broadband techniques was small and well controlled. The NO3Comp campaign demonstrated the high quality, reliability and robustness of performance of current state-of-the-art instrumentation for NO3 detection.